Stage at Diagnosis and Patient Delay among Breast Cancer Women in Kabul, Afghanistan - Behrad, Mohammad Sayed; Rashed, Firoozeddin; Zarabi, Attaullah; Saidi, Surya (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Breast cancer is the commonest cause of mortality among women. According to WHO in 2012, about 7400 women died because of cancers in Afghanistan. Aim: To obtain information about clinical stages of breast cancer of women at the time of diagnosis in Kabul, Afghanistan. Patient and Method: This was a cross-sectional study of 240 women diagnosed with breast cancer from March 2016 to March 2019. The diagnosis of breast cancer was made by the surgeon on the basis of physical examination and Biopsy/Pathological reports. Clinical staging of the tumor was recorded according to the tumor, nodal, and metastasis (TNM) classification. The gap between knowing the problem and consulting a physician (Patient delay) was categorized: less than 3 months, 3-6 months and more than 6 months. Results: The mean age of patients was 49.31 years (SD ± 11.80) ranging from 18 to 76 years. The Patient delay was more than 6 months (65%). Infiltrating ductal carcinoma was the commonest morphological type (76.7%). Breast cancer in left breast of patients was 52.1%. Stage II was higher in left and stage III in right breast. The majority of patients were in stage II & III at the time of diagnosis. All stages were frequent in fourth decades of age group. The association between the clinical stages of breast cancer at the time of diagnosis, the age and breast R/L involvement of the patients was significant (P<0.001). The association between clinical stage and marital status was not significant (P<0.953). Conclusion: Late referrals, diagnosis delay and advanced stages of breast cancer are still a serious problem in Afghanistan. Cancer in right breast should be given more attention because higher stages of the disease are expected. Awareness and social education is great need.